Impact of Trade Liberalization on Foreign Direct Investment in Indian Industries - Bishwanath Goldar; Rashmi Banga (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
The paper undertakes analyses at three levels and the results arrived at different levels indicate that trade liberalization has had a favourable effect on FDI flows in India. It is also found that the regions having greater extent of international trade are able to attract greater amount of FDI. Some evidence is found that point to differential effects of trade associated with international vertical integration and intra-industry trade. Though liberalization has led to a substantial increase in intra-industry trade, much of the intra-industry being horizontal in nature in India is not found to have a strong favourable effect on FDI.
Keywords: F1; 330; Trade Liberalization; Foreign Direct Investmetn; India; Indian Industries